2020
DOI: 10.47203/ijch.2020.v32i03.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge and Awareness regarding COVID-19 Disease among Medical and Dental students in Saudi Arabia

Abstract: Objective: To evaluate the levels of information regarding the current emerging outbreak of coronavirus disease 2019 (COVID-19) among medical and dental students at universities in Saudi Arabia through an online questionnaire. Methods: A detailed structured questionnaire was prepared, containing demographic profiles and questions related to knowledge and awareness of the COVID-19 pandemic, and was emailed to 240 subjects, out of these, 209 responded to all the questions. Results: The majority of the respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
3
8
1
Order By: Relevance
“…Good knowledge about the causative factors, the virus, and the routes of transmission can be attributed to the availability of information in the electronic media such as television, radio, social networking sites, and different websites. These findings were also seen in a study done among university students in Jordan and Saudi Arabia [20,23,27].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Good knowledge about the causative factors, the virus, and the routes of transmission can be attributed to the availability of information in the electronic media such as television, radio, social networking sites, and different websites. These findings were also seen in a study done among university students in Jordan and Saudi Arabia [20,23,27].…”
Section: Discussionsupporting
confidence: 70%
“…Our study showed that only 71% of students were aware about the mode of transmission of this virus, which is lesser compared to similar studies from India and Saudi Arabia among students, where 91% and 98.1% of students knew about the transmission modes and the signs and symptoms of the disease [22,23]. A study from Jordan evaluated the knowledge of transmissions of infection from one infected individual to others [19].…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations